Obituary for John Cammett: Organic Intellectual - Davidson, Alastair (International Gramsci Journal, 2023)
John Cammett, died on July 30, 2008. Internationally known as a pioneering scholar of Antonio Gramsci, he studied the impact of Gramsci on the Italian communist movement, which became the most significant aspect of his life’s work.